2014
DOI: 10.1080/00222348.2014.943629
|View full text |Cite
|
Sign up to set email alerts
|

Nanosurface Mechanical Properties of Polymers Based on Continuous Stiffness Indentation

Abstract: A systematic experimental study of the large strain surface mechanical properties of a number of polymers {polymethylmethacrylate (PMMA), polyetheretherketone (PEEK), polystyrene (PS), polycarbonate (PC), polypropylene (PP), and ultra-high molecular weight polyethylene (UHMWPE)} at the nanometer scale is described. The polymeric surfaces were indented and the data were analyzed using a contact compliance method in conjunction with a nano-indenter system. The indentation experiments were performed using a Berko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…These values of hardness and modulus are in close agreement with the already reported values of hardness (40 MPa) and modulus (1.3 GPa) of Figures 2 and 3 also show a significant increase in hardness (from 27 to 70 MPa at a displacement of 4000 nm) and modulus (from 0.9 to 2.0 GPa at a displacement of 4000 nm) by increasing the vibration amplitude from 1 to 10 nm. These values of hardness and modulus are in close agreement with the already reported values of hardness (40 MPa) and modulus (1.3 GPa) of UHMWPE at 45 Hz and 1 nm [9]. In addition, the effect of indentation frequency on the load-displacement curves, hardness, and modulus of UHMWPE, at a vibration amplitude of 2 nm at The effect of different indentation depths on the nano-mechanical properties of UHMWPE was also analyzed at 45 Hz and 1 nm and the results are presented in Figures 7 and 8.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…These values of hardness and modulus are in close agreement with the already reported values of hardness (40 MPa) and modulus (1.3 GPa) of Figures 2 and 3 also show a significant increase in hardness (from 27 to 70 MPa at a displacement of 4000 nm) and modulus (from 0.9 to 2.0 GPa at a displacement of 4000 nm) by increasing the vibration amplitude from 1 to 10 nm. These values of hardness and modulus are in close agreement with the already reported values of hardness (40 MPa) and modulus (1.3 GPa) of UHMWPE at 45 Hz and 1 nm [9]. In addition, the effect of indentation frequency on the load-displacement curves, hardness, and modulus of UHMWPE, at a vibration amplitude of 2 nm at The effect of different indentation depths on the nano-mechanical properties of UHMWPE was also analyzed at 45 Hz and 1 nm and the results are presented in Figures 7 and 8.…”
Section: Methodssupporting
confidence: 92%
“…Therefore, knowledge of the surface properties are important considerations for material selection and design in applications involving surface engineering and tribological contacts. The mechanical properties of the outermost surface layers have been conveniently investigated using the nano-indentation technique for the past two decades by us and a number of other researchers [6][7][8][9][10][11][12][13][14][15][16][17][18]. Nano-indentation, a non-destructive technique, is a powerful tool for analyzing the surface mechanical properties of a wide variety of materials, including polymers, metals, composites, and biological entities.…”
Section: Introductionmentioning
confidence: 99%
“…An abrupt increase in hardness was recorded by R. Krache et al when PC phase inversion occurred from dispersed to continuous phase [3]. T. Iqbal et al used nano-indentation to determine surface mechanical properties of PC and reported hardness of 0.2 ± 0.02 GPa [15]. Interestingly, the blend sample 50% ABS/50% PC exhibited a significantly lower hardness value of 0.16 GPa compared to the values of 0.22 and 0.27 GPa for neat ABS and PC, respectively.…”
Section: Nano-indentationmentioning
confidence: 97%
“…Surface mechanical properties of some polymers such as polymethyl methacrylate (PMMA), polyetheretherketone (PEEK), polystyrene (PS), polycarbonate (PC), polypropylene (PP), and ultra-high molecular weight (UHMWPE) were discussed by T. Iqbal et al using continuous stiffness nano-indentation. Considerable strain-rate hardening effect was observed for these polymers, with PMMA giving maximum hardness values [15]. Experimentation has been conducted to determine surface mechanical properties of viscous materials [16], polycarbonate, and syndiotactic polystyrene [17], polycarbonate/polymethyl methacrylate [18], poly(lactic acid)-based composites [19], α-Al 2 O 3 (0001) [20], and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoindentation, also called the depth-sensing method, was proposed by Oliver and his co-workers in 1992 and is used to determine the surface mechanical properties of solid materials [23]. The contact compliance method is basically adopted in the nanoindentation for evaluating the data analysis to avoid the error occurred during the conventional hardness technique [24]. Reaction force on the indenter was measured as a function of imposed depth by applying the contact compliance method, or vice versa, creating the loading-unloading cycles during indentation on the material surface [23].…”
Section: Characterizationmentioning
confidence: 99%